Between European and Muslim-Majority Civil Law Systems: Comparative Supervisory Liability in France, Iraq, and Egypt - Atroshi , Hozan Abdulmohsin Abdullah (UIN Sunan Kalijaga, 2026)
This study examines the legal foundations of supervisory liability under French civil law through a comparative analysis with Iraqi and Egyptian legislation. It centers on the evolution of liability for the actions of others, with particular emphasis on Article 1242 of the French Civil Code, and assesses the shift in French jurisprudence from a restrictive interpretation toward the acknowledgment of a general principle of liability, especially following the seminal Blieck decision of 1991. The research explores whether supervisory liability is predicated on presumed fault, risk theory, guarantee, representation, or substitution, and juxtaposes these bases with Articles 218, 219, and 191 of the Iraqi Civil Code and Article 173 of the Egyptian Civil Code. Employing a doctrinal and analytical methodology, the study examines statutory provisions, judicial rulings, and prominent juristic opinions across the three legal systems. The findings reveal that French and Egyptian law primarily adopt a rebuttable presumption of fault as the foundation of supervisory liability, whereas Iraqi law integrates presumed fault with aspects of guarantee-based responsibility derived from Islamic jurisprudence.